Digitalization of Financial Literacy and Social Media as a Sustainable Economic Strategy in Food & Beverages: Digitalisasi Literasi Keuangan dan Media Sosial sebagai Strategi Ekonomi Berkelanjutan pada Food & Beverages - Hamdan, Hamdan; Nabila, Efa Ayu; Gunawan, Reyhan Algiffary; Valentie, Ajeng Putri; Perez, Carlos (ADI Publisher, 2025)
The digitalization of financial literacy is a crucial foundation for strengthening the resilience and economic sustainability of the Micro, Small, and Medium Enterprises (MSMEs) sector, particularly in the dynamic and competitive food and beverage industry. This study aims to analyze the role of creative communication strategies, brand personality, and digital marketing engagement in encouraging the optimization of interactive social media and the utilization of user-generated content as instruments for improving MSME financial literacy. Using quantitative methods and a Structural Equation Modeling (SEM) approach based on SmartPLS software, this study involved 150 MSMEs in the food and beverage sector across Indonesia. The results show that creative communication strategies and brand personality have a significant influence on digital marketing engagement, which in turn encourages social media use and consumer participation in producing educational content. These findings confirm that the digitalization of financial literacy through digital platforms not only improves financial understanding but also strengthens MSME businesses position in a sustainable digital economy ecosystem. This study provides strategic implications for MSMEs, policymakers, and other stakeholders in developing social media-based financial literacy models relevant to the characteristics of the food and beverage sector.